Legal pluralism and efficiency in marriage law / Rorick Tovar Galván. - Tovar Galvan, Rorick (Intersentia, 2022)
Based on economic theory, this book offers a novel approach to understanding the marital dynamic, explaining the substantive regulation of marriage and modeling legal outcomes at the conflict of laws level. On this ground the author proposes specific rules to regulate the party autonomy for the law governing the relationship, and to determine the applicable law in absence of a choice of law agreement for key aspects of the relationship: maintenance obligations, divorce, and property regime. The book is organized in two parts, preceded by an introductory section, where the results achieved by the harmonization of conflict rules promoted by the EU are examined critically. The first part puts forward economics as the approach to better comprehend the couple's expectations of marriage. It focuses on explaining the economic rationale behind marriage, underlining its contractual nature, and demonstrating that common legal remedies as well as several mandatory and default rules in modern marriage law indeed have an economic foundation. The second part is devoted entirely to the conflict of laws dimension of marriage. The book will therefore be of interest to scholars and lawmakers attempting to launch reforms anywhere or looking for a practical and novel application of economics in the analysis of the law.